HIGH-PRECISION 142ND/144ND MEASUREMENTS IN TERRESTRIAL ROCKS: CONSTRAINTS ON THE EARLY DIFFERENTIATION OF THE EARTH'S MANTLE - Caro G.; Bourdon B.; Birck J.L.; Moorbath S. (My University, 2006)
We present new ultra-high precision 142Nd/144Nd measurements of early Archaean rocks using the new generation thermal ionization mass spectrometer Triton. Repeated measurements of the Ames Nd standard demonstrate that the 142Nd/144Nd ratio can be determined with external precision of 2 ppm (2σ), allowing confident resolution of anomalies as small as 5 ppm. A major analytical improvement lies in the elimination of the double normalization procedure required to correct our former measurements from a secondary mass fractionation effect. Our new results indicate that metasediments, metabasalts, and orthogneisses from the 3.6 to 3.8 Ga West Greenland craton display positive 142Nd anomalies ranging from 8 to 15 ppm. Using a simple two-stage model with an initial ε143Nd value of 1.9 ± 0.6 ε-units, coupled 147Sm-143Nd and 146Sm-142Nd chronometry constrains mantle differentiation to 50-200 Ma after formation of the solar system. This chronological constraint is consistent with differentiation of the Earth's mantle during the late stage of crystallization of a magma ocean. We have developed a two-box model describing 142Nd and 143Nd isotopic evolution of depleted mantle during the subsequent evolution of the crust-mantle system. Our results indicate that early terrestrial protocrust had a lifetime of ca. 0.7-1 Ga in order to produce the observed Nd isotope signature of Archaean rocks. In the context of this two box mantle-crust system, we model the evolution of isotopic and chemical heterogeneity of depleted mantle as a function of the mantle stirring time. Using the dispersion of 142Nd/144Nd and 143Nd/144Nd ratios observed in early Archaean rocks, we constrain the stirring time of early Earth's mantle to 100-250 Ma, a factor of 5 shorter than the stirring time inferred from modern oceanic basalts. © 2005 Elsevier Inc. All rights reserved.